ANALISIS LIVING QURAN TERHADAP TRADISI SEWELASAN DI PESANTREN AL-MARDLIYYAH TAMBAKBERAS JOMBANG - Muthi'ah Hijriyati (Menara Tebuireng, 2020)
Interactions between Holy Koran and humans often experience differences from studies of the interpretation of the Holy Koran itself. People’s responses to the Koran and its practice become a separate phenomenon that deserves to be examined. Because the study of the Koran does not always have to be centered on the study of texts alone, the public response to the Koran can become a new stream of contemporary Koran study research. Considering that the study of ansikh's Koran study cannot capture the social reception of the people of the Koran. The phenomenon of the Koran that "lives" in the community certainly requires a study of social science and anthropology. This is why the study of the Living Quran is a new direction in the study of religious anthropology. But even so, the formal object is still in the study of the Koran and its understanding, the implementation and belief of certain people in the Koran, and the extent to which the embodiment of the Koran in its daily life (Al-Quran in Everyday life). Therefore, the Living Quran Analysis of the Sewelasan tradition in the al-Mardliyyah Islamic School in Tambakberas Jombang is interesting to study, with the Living Quran approach, it can be understood as to what purpose, and how the Sewelasan practice is implemented. From this it can also be explored how the reception of santri al-Mardliyyah on the interpretation of the verse about Allah's guarantee of the preservation of the Koran.